Capitalismo mediático e marketing: uma análise crítica sobre o uso das redes sociais nas ações e práticas de marketing - Silva, Érico de Paula (2017)
The present research deals with social network websites as products derived from the mediatic capitalism. It was identified a historical alignment in the logic and principles between: capitalism, communication networks and social networks. A paradox was identified in these sites, where spectralised subjects simultaneously constitute and are captured through a power strategy which transforms information into demographic data - public (consumer) profiles. These sites are understood here as the ultimate device of media visibility in the context of cyber-cultural media capitalism. The focus is on in-depth study of Facebook’s products and services offered to corporate capital for Marketing actions. Finally, how capital has appropriated this media environment, turning it into a kind of big data of Marketing. From this perspective, the following questions are raised: (1) what is the function and social significance of these social network websites in the context of media capitalism in its cyberculture stage? (2) is it possible to state that the appropriative practices of communication tools in this media environment are configured as a means of capture? We work with the following hypotheses: (1) these cyber-cultural products popularly known as social networks are typical products of media capitalism and are historically aligned with the logic and principles of communication networks and capitalism; (2) such websites could be understood as technological capture devices, which translate circulating information (individual and / or collective) into demographic data, capable of segmenting, recombining and organizing people into groups and such groups in "target audiences" for Marketing actions. The aim is to provide a critical analysis of the role of these online environments in the corporate capital and an understanding of their sociocultural significance in the current phase of capitalism. The research uses the concepts and definitions about media capitalism (Perry Anderson, Frederic Jameson and David Harvey); about social networks (Danah Boyd, Nicole Ellyson, Daniel Parrochia, Silvia Portugal); in the perspective of the critical epistemology of cyberculture (Eugênio Trivinho); and biopower / control society (Michel Foucault, Gilles Deleuze and Giorgio Agamben, Antônio Negri, Michael Hardt,); and the theoretical foundation related to marketing techniques, practices, discourses and actions (Phillip Kotler, Peter Drucker). Therefore, the idea is to contribute to the critical studies on Marketing actions and practices projected through the appropriation of the new communication technologies in the environment of media visibility